Tax Service Quality, Trust in Government and Tax Compliance among Small and Medium Enterprises in North Rift Economic Bloc - Amos Kiptum; Collins Kapkiyai; Daniel Kirui (SEISENSE Journal of Management, 2024)
Purpose- The study sought to establish the indirect effect of trust in government on the relationship between the tax service quality and tax compliance among SMEs in North Rift Economic Bloc, Kenya.Design/Methodology- Based on the social contract theory, this study has a positivist philosophy that is informed by an explanatory research design. The target population was 21,232 SMEs; the sample size used in this study consisted of 393 SME owners/managers selected through a stratified sampling technique. Data were collected using a self-administered questionnaire, and Cronbach's alpha with factor analysis was used to establish the instrument's reliability and validity. Descriptive and inferential statistics were employed to test the hypothesis, and hierarchical regression using the Hayes Process macro was performed.Findings-The study revealed that tax service quality (β =.541, p=.000<0.05) and trust in government (β =.375, p=.000<0.05) are significantly positively related to tax compliance. In addition, the tax service quality was found to have a significant effect on trust in government (β =.395, p =.000<0.05). In addition, the results showed that trust in government mediates the relationship between tax service quality and tax compliance (β =.1482, CI=.0981, .2015).Practical Implications- These findings underscore the need for governments to improve the quality tax services, as this may be able to help in gaining public trust which will ultimately increase SMEs compliance with taxes. There is scope for future research to incorporate mixed-method approaches in order to discover yet more factors affecting tax compliance.